Identifikasi Keragaman Mikroflora dan Pengaruhnya pada Kualitas Organoleptik Tempoyak Khas Suku Dayak di Kalimantan Tengah - Swestyani, Sondra; Hujjatusnaini, Noor (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Tempoyak as local wisdom and national culture is poorly documented. Therefore, it is important to explore the preferences of the millennial generation regarding the organoleptic qualities of Tempoyak. The research design is a one-shot case study. The variables tested were the diversity of microflora in tempoyak, and its influence on the level of organoleptic quality and the level of preference of the millennial generation. Identification of isolates using API-50CHL, biochemical tests and physiological tests. Organoleptic quality uses the hedonic scale test. The research panelists were 120 people from the Dayak, Madura, Jawa and Banjar tribes. Data analysis uses one way Anava analysis. 15 isolates of microflora were found in Tempoyak which affected its taste and organoleptics, 8 isolates including lactic acid bacteria, including Pediococcus acidilactici, Lactobacillus curvatus, Leuconostoc mesenteroides, Lactobacillus plantarum, Streptococcus thermophiles, Lactobacillus pentosus, Enterococcus faecium, and Weissella paramesenteroides. 1 isolate of non-lactic acid bacteria that is Micrococcus varians. 2 isolates from the yeast group consisted of Saccharomyces cereviciae and Kluyveromyces marxianus, and 4 isolates included Rhizopus, Monilia sitophila, and Mucor roxii. All microflora found were capable of producing lactic acid, except Aspergillus repens. The statistical test results show the significance of its influence on the organoleptic quality of all sub-variables, including color, taste, aroma and texture of Tempoyak. The exploration results in this research indicate opportunities for Tempoyak to be more developed, innovative and contemporary, so that it is preferred by the millennial generation.